Concatenator: sequence data matrices handling made easy - Pina-Martins, Francisco (2020)
Concatenator is a simple and user-friendly software that implements two very useful functions for phylogenetics data analysis. It concatenates NEXUS files of several fragments in a single NEXUS file ready to be used in phylogenetics software, such as paup and mrbayes and it converts FASTA sequence data files to NEXUS and vice-versa. Additionally, concatenated files can be prepared for partition tests in paup. It is freely available in http://cobig2.fc.ul.pt.